Memotret Wajah Ruang Publik melalui Sistem Penamaan Perumahan di Kota Malang: Kajian Lanskap Linguistik - Dany Ardhian; Eti Setiawati Eti; Millatuz Zakiyah Mila (Ikaprobsi, 2023)
The naming system of residential areas serves not only as a strategy to influence consumers but also as a reflection of the characteristics, behaviors, lifestyles, and social motivations of a region's community. This research aims to investigate the forms and patterns of language usage, analyze collocation relationships, and examine the information-symbolic functions of language use. Data were collected from 257 texts on housing signs in five districts of Malang City: Lowokwaru, Klojen, Blimbing, Sukun, and Kedung Kandang. The data source for housing signs was collected using documentation techniques (photography). Interviews were conducted with a number of developers and homebuyers. The data were analyzed using corpus linguistics (LancsBox software version 6.0) and the linguistic landscape framework proposed by Landry and Bourhis. The research results indicate that five languages are involved in the residential naming system, namely Indonesian, English, Arabic, Spanish, and Japanese. The use of Indonesian and English is extensive in the housing naming system, and both languages are involved in all patterns, including monolingual, bilingual, and multilingual. Some other languages, such as Javanese, Arabic, and Japanese, are also present but in a more varied manner. Corpus linguistic analysis also shows that the lexicons